Polyphasic Temporal Behavior of Finger-Tapping Performance: A Measure of Motor Skills and Fatigue. - Aydin, Leyla; Kiziltan, Erhan; Gundogan, Nimet Unay (Journal of Motor Behavior)
Successive voluntary motor movement involves a number of physiological mechanisms and may reflect motor skill development and neuromuscular fatigue. In this study, the temporal behavior of finger tapping was investigated in relation to motor skills and fatigue by using a long-term computer-based test. The finger-tapping performances of 29 healthy male volunteers were analyzed using linear and nonlinear regression models established for inter-tapping interval. The results suggest that finger-tapping performance exhibits a polyphasic nature, and has several characteristic time points, which may be directly related to muscle dynamics and energy consumption. In conclusion, we believe that future studies evaluating the polyphasic nature of the maximal voluntary movement will lead to the definition of objective scales that can be used in the follow up of some neuromuscular diseases, as well as, the determination of motor skills, individual ability, and peripheral fatigue through the use of a low cost, easy-to-use computer-based finger-tapping test.